Phenotypes of Pain Behavior in Phospholipase C-Related but Catalytically Inactive Protein Type 1 Knockout Mice. Issue 1 (18th October 2011) - Migita, Keisuke; Tomiyama, Masahiko; Yamada, Junko; Fukuzawa, Masashi; Kanematsu, Takashi; Hirata, Masato; Ueno, Shinya
Phospholipase C-related inactive protein (PRIP) plays important roles in trafficking to the plasma membrane of GABAA receptor, which is involved in the dominant inhibitory neurotransmission in the spinal cord and plays an important role in nociceptive transmission. However, the role of PRIP in pain sensation remains unknown. In this study, we investigated the phenotypes of pain behaviors in PRIP type 1 knockout ( PRIP-1 −/− ) mice. The mutant mice showed hyperalgesic responses in the second phase of the formalin test and the von Frey test as compared with those in wild-type mice. In situ hybridization studies of GABAA receptors revealed significantly decreased expression of γ2 subunit mRNA in the dorsal and ventral horns of the spinal cord in PRIP-1 −/− mice, but no difference in α1 subunit mRNA expression. β2 subunit mRNA expression was significantly higher in PRIP-1 −/− mice than in wild-type mice in all areas of the spinal cord. On the other hand, the slow decay time constant for the spontaneous inhibitory current was significantly increased by treatment with diazepam in wild-type mice, but not in PRIP-1 −/− mice. These results suggest that PRIP-1 mice exhibit the changes of the function and subunits expression of GABAA receptor in the spinal cord, which may be responsible for abnormal pain sensation in these mice.